an analysis of efficiency and loan loss provisioning behavior in Chinese banking - he, jing (2017)
This study examines Cost Efficiency and Loan loss provisioning in China commercial banks between the years 2011-2015 for a sample of 63 banks. While much research explores discretionary provision determinants we argue that it is also important to access non-discretionary determinants of loan loss provisioning as well. So along with income smoothing, capital management hypothesis we further investigate cost efficiency and bank Z-score as possible determinants of loan loss provisions. To do so we use Cost efficiency function using SFA and a dynamic system GMM is used for Loan loss provisions model. We find that for Chinese commercial banks income smoothing hypothesis apply and Efficiency is an important determinant of loan loss provisions in China.